2022
DOI: 10.1002/jcaf.22540
|View full text |Cite
|
Sign up to set email alerts
|

Director co‐option and the cash conversion cycle

Abstract: This study examines whether co-opted directors degrade or improve working capital efficiency. We find strong evidence that firms with more co-opted boards exhibit lower cash conversion cycles and so are more efficient at managing working capital. After controlling for other factors, board co-option reduces the length of the cash conversion cycle by about −1.2%, whereas the co-option of independent directors reduces the cycle by nearly −2.0%. These results persist even after addressing endogeneity and are robus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Also, the quick ratio and inventory turnover ratio is a moderate negative correlation (r=-.476). (Badakhshan & Ball, 2022;Harris & Hampton, 2022;Azam, 2022). The coefficient of determination, or R Squared, shows the overall variance in the dependent variable.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the quick ratio and inventory turnover ratio is a moderate negative correlation (r=-.476). (Badakhshan & Ball, 2022;Harris & Hampton, 2022;Azam, 2022). The coefficient of determination, or R Squared, shows the overall variance in the dependent variable.…”
Section: Resultsmentioning
confidence: 99%
“…A decrease in the corporate CCC will increase profitability (Abolfathi et al, 2022). Numerous studies have examined the relationship between WCM and profitability and found a negative relationship between the cash conversion cycle and profitability (Soda et al, 2022;Harris & Hampton, 2022;Garg & Meentu, 2022). Richards & Laughlin (1980) came up with the concept of CCC.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Industry‐adjusted days payable outstanding ( ADJ_DPO ) is the average account payables divided by cost of goods sold minus the industry‐year mean at the end of the fiscal year before the attack. Lower ADJ_DIO and ADJ_DRO values imply that firms are better at selling products and collecting cash from customers than their rivals, whereas higher ADJ_DPO values indicate that firms get more favorable trade credit terms from suppliers than their peers (Harris & Hampton, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…As board co‐option helps insulate managers with career concerns, it should give these managers a stronger incentive to pursue risky, value‐enhancing projects. Existing literature finds that board co‐option is associated with a greater inclination towards LGBT‐supportive policies (Kyaw et al, 2021), higher R&D investments and innovation (Chintrakarn et al, 2016; Nguyen et al, 2020), and more efficiently managing working capital (Harris & Hampton, 2022).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%